Effectiveness of a multimodal medico-psychological correction program in servicemembers and veterans with chronic pain: a controlled study - Nikolaieva Олександра (Psychosomatic Medicine and General Practice, 2026)
Background. Chronic pain with a neuropathic component in servicemembers and veterans is frequently accompanied by depression, anxiety and posttraumatic stress disorder, responds poorly to standard pharmacotherapy and requires a comprehensive approach. Evidence on structured multimodal medico-psychological correction programs for this population remains limited. Aim. To evaluate the effectiveness of a multimodal medico-psychological correction program in servicemembers and veterans with chronic pain with a neuropathic component compared with standard physical rehabilitation. Methods. A prospective controlled study was conducted with 181 male patients. The main group (n=91) underwent a seven-module multimodal medico-psychological correction program combined with physical rehabilitation; the control group (n=90) received physical rehabilitation only. Assessment was performed using the PHQ-9, GAD-7, PCL-5, DN4, Visual Analogue Scale (VAS) and MoCA at admission (T0), discharge (T1) and 3 months later (T2). Data were analyzed in IBM SPSS Statistics 26.0 using the Wilcoxon test, the Mann–Whitney test and analysis of covariance (ANCOVA). Results. The main group showed statistically significant improvement across all measures with large effect sizes (r=0.70–0.86; all p<0.001), which straightened by the third month of follow-up. The control group demonstrated markedly weaker dynamics (r=0.22–0.61). Between-group comparison (Mann–Whitney test and ANCOVA) revealed significantly greater improvement in the main group across all scales (all p<0.001; for MoCA p=0.002), which persisted after adjustment for baseline values. Discussion. The findings indicate an independent contribution of the multimodal program to the recovery of psychoemotional state, reduction of pain intensity and its neuropathic component, and improvement of cognitive functioning. The sustained and delayed nature of the effect suggests the formation of self-regulation skills in patients. Conclusions. Integrating a structured multimodal medico-psychological correction program into the rehabilitation process provides substantially greater and more sustained improvement than physical rehabilitation alone and supports its implementation for servicemembers and veterans with chronic pain with a neuropathic component. Keywords: chronic pain, neuropathic pain, medico-psychological correction, multimodal program, servicemembers, veterans, rehabilitation.